Pollution, untouchabiligy and harijans : a south Indian ethnography - Sekine, Yasumasa (Rawat Publications, 2011)
This book critically examines the widely circulated Dumontian approach of "pure-impure" ideology in the context of social pollution in India, as this concept sees pollution as an object of repression and rejection and, as such, is a negative concept. To overcome the limitations of this concept, the book argues that "pollution" and "impurity" may not be the same, and that, in reality, the very marginal nature of pollution facilitates for a creative space - a space with hidden potential for decentralization - where it is possible to radically change one's own sense of order through encounters with others. With this realistic view, the cultural realities of India's Harijans (untouchables) are discussed, by interpreting the rituals and daily behavior of villagers across their socio-economic situations, caste positions, and lineage. This observation - in the context of a comparison to the upper castes - makes it clear that the Harijans are led by a desire for improvements in the quantity and quality of life and live strategically within the same core reality of "pollution" ideology as the upper castes. The book points out that the stereotyped image of the Indian society as "an alien and incomprehensible society that still maintains a discriminatory caste system" is to be reconsidered and set right.